About trials of using term of alienation for conceptualisation of moral corruption process - Biegasiewicz, Monika (Studia Psychologica: Theoria et praxis, 2011)
This article is a trial of understanding the process of moral eorruption of young people in the context of their feeling of social alienation. It is underlined that the term of moral eorruption is a legal term with a pejorative tinge that has no psychological designatum. This article presents a conception of M. Seeman alienation with an emphasis on five categories distinguished by the author: self estrangement, powerlessness, social isolation, meaninglessness and formlessness. On the base of Seemana’s theory, K. Kmiecik-Baran has constructed the Scale of Feeling and Integration which she has enriched Seemans categories with their opposing dimensions: self-estrangement authonomy, powerlessness self reliance, social isolation social integration, meaninglessness sense, normlessness social order. This article gets closer the theoretical foundations of scale and it contains a description of causes and consequences of alienation from the developmental perspective. The destructive ways of managing the alienation described in the article such as drinking alcohol, taking intoxicant, rebellion against the social norms, creating or belonging to groups of destructive nature are behaviours, which according to law, (the Act of juvenile processes) are the evidence of moral corruption. This is the recommendation to use the model of Alienation and Integration to describe and understand the process of moral corruption.